IMPROVING GRADUATES' COMPETENCE THROUGH SCHOOL PRINCIPAL LEADERSHIP AND TEACHER PERFORMANCE AT SCHOO - Mania, Majidah Aqifah; Rohimat, Hendi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The problem studied in this research is the lack of optimal competency of SMAIT Qordova School graduates, Bandung Regency. The problem of absorbing graduates who are not yet able to compete is due to the low quality of graduates. This is a phenomenon of the quality of graduate competence not being optimal. This research is intended to obtain the educational concept of SMAIT Qordova Bandung Regency in improving the quality of graduate competency so that it can produce graduates who are qualified and in line with future needs. The method used in this research is the Explanatory Survey Method. The data collection technique uses an ordinal scale questionnaire. The number of respondents was 21 educators, taken as a whole from teachers at SMAIT Qordova. Data processing techniques use Path Analysis Models. In detail, the results of this research show that: (1) The principal's leadership has a strong, positive and significant influence on teachers' teaching performance and management of learning facilities; (2) The principal's leadership and the teacher's teaching performance have a positive and significant effect on the learning process; (3) The principal's leadership, teacher's teaching performance, and the learning process have a positive and significant effect on the quality of graduate competency